Does measurement technique explain the mismatch between European head size and WHO charts?. Issue 7 (16th December 2016) - Wright, Charlotte M; Bremner, Morven; Lip, Stefanie; Symonds, Joseph D
Abstract : Objective: To test whether different measuring techniques produce systematic differences in head size that could explain the large head circumferences found in Northern European children compared with the WHO standard. Design: Cross-sectional observational study. Setting: Scotland, UK. Patients: Study 1: 68 healthy children aged 0.4–18 months from mother and baby groups and a medical students teaching session. Study 2: 81 children aged 0.4 to 25 months from hospital wards and neonatal follow-up clinics. Interventions: Study 1: heads measured with plastic tape using both the WHO tight and UK loose technique. Study 2: heads measured using WHO research technique and a metal measuring tape and compared with routinely acquired measurements. Main outcome measures: Mean difference in head z-scores using WHO standard between the two methods. Results: The tight technique resulted in a mean (95% CI) z-score difference of 0.41 (0.27 to 0.54, p<0.001) in study 1 and 0.44 (0.36 to 0.53, p<0.001) in study 2. However, the mean WHO measurements in the healthy infants still produced a mean z-score that was two-third of a centile space (0.54 SD (0.28 to 0.79) p<0.001) above the 50th centile. Conclusion: The WHO measurement techniques produced significantly lower measures of head size, but average healthy Scottish children still had larger heads than the WHO standard using this method.